The occurrence of caffeine in surface waters for public supply - Carvalho, Ana Carla Coleone de; Silva, Bianca Ferreira da; Machado, Angela Aparecida [UNESP]; Santarossa, Maria Amália da Silva [UNESP]; Paganini, Wanderley da Silva (FapUNIFESP (SciELO), 2022)
With an intense consumption and continuous release into domestic and industrial effluents, caffeine has been regularly detected in aquatic environments worldwide. This psychoactive is considered an excellent indicator of contamination in water, related to human activity. However, the impacts it can have on health and on the environment are still not well understood. Thus, the objective of this work was to verify the presence of caffeine in raw water treated by a conventional water treatment plant, in different hydrological periods, and to evaluate the potential risk that it represents to the aquatic environment. Caffeine was detected in all raw water samples. The highest concentration was observed in the most intense period of drought. It was not detected in the treated water. The compost is considered to be of high risk to the aquatic environment. The results indicate the vulnerability of the source in question.
A ocorrência de cafeína em águas superficiais para abastecimento público
Keywords: drinking water; environmental risk; liquid chromatography; mass spectrometry; raw water